263 brain busters : just how smart are you, anyway? - Phillips, Louis 1942-; Stevenson, James 1929-2017 (New York : Puffin Books, 1985)
A collection of mathematical and verbal brain-teasing questions interspersed with "brain vacation" jokes.
U
900
U
Keywords: Puzzles -- Juvenile literature; Mathematical recreations -- Juvenile literature; Literary recreations -- Juvenile literature; Puzzles; Mathematical recreations; Literary recreations